Functions of the CSB Protein at Topoisomerase 2 Inhibitors-Induced DNA Lesions - Busatto, Franciele Faccio; Mersaoui, Sofiane Y.; Sun, Yilun; Pommier, Yves; Masson, Jean-Yves; Saffi, Jenifer (Frontiers in Cell and Developmental Biology, 2021)
Topoisomerase 2 (TOP2) inhibitors are drugs widely used in the treatment of different types of cancer. Processing of their induced-lesions create double-strand breaks (DSBs) in the DNA, which is the main toxic mechanism of topoisomerase inhibitors to kill cancer cells. It was established that the Nucleotide Excision Repair pathway respond to TOP2-induced lesions, mainly through the Cockayne Syndrome B (CSB) protein. In this paper, we further define the mechanism and type of lesions induced by TOP2 inhibitors when CSB is abrogated. In the absence of TOP2, but not during pharmacological inhibition, an increase in R-Loops was detected. We also observed that CSB knockdown provokes the accumulation of DSBs induced by TOP2 inhibitors. Consistent with a functional interplay, interaction between CSB and TOP2 occurred after TOP2 inhibition. This was corroborated with in vitro DNA cleavage assays where CSB stimulated the activity of TOP2. Altogether, our results show that TOP2 is stimulated by the CSB protein and prevents the accumulation of R-loops/DSBs linked to genomic instability.